Analysis of Cognitive Diagnostic Assessment of the Indonesian Language Subject for Fourth Grade Students - Andriani, Rizki; Asyraf Suryadin; Dody Pranata (Journal of Practice Learning and Educational Development, 2026)
Cognitive diagnostic assessment serves as a tool to evaluate and identify students’ cognitive abilities. This study investigates its implementation in the Indonesian language subject for fourth-grade students at UPTD SD Negeri 8 Belinyu. Employing a qualitative descriptive approach, the research utilized eight assessment indicators: four focusing on students and four on teachers. Both students and teachers were included as participants, while data were gathered through interviews, observations, and documentation, then systematically analyzed. Findings indicate that students’ ability profiles (Indicator 1) averaged a score of 3, classified as moderate. Potential strengths (Indicator 2) scored between 3 and 4, suggesting opportunities for adaptive strategy development. Potential weaknesses (Indicator 3) scored 3, indicating situational constraints. Students’ cognitive capacity (Indicator 4) scored 3–4, reflecting readiness to engage in learning. Among teacher-related indicators, remedial instruction (Indicator 5) was implemented optimally with a score of 4, whereas learning support distribution (Indicator 6) scored 3, showing uneven provision. Learning alignment with curriculum standards and objectives (Indicator 7) and clarity in individual assessment (Indicator 8) both scored 4. In conclusion, cognitive diagnostic assessment contributes positively to students’ academic achievement, offering a structured and sustainable framework for enhancing learning outcomes at both individual and class levels.